2023
DOI: 10.1021/acs.est.2c08520
|View full text |Cite
|
Sign up to set email alerts
|

First Measurements on Triple Oxygen Isotopes of Dissolved Inorganic Phosphate in the Hydrosphere

Abstract: Although dissolved inorganic phosphate (DIP) is an important nutrient in the hydrosphere, it is difficult to quantitatively clarify the dynamics of DIP in the hydrosphere using the δ18O value of DIP as a tracer. In this study, we quantified the triple oxygen isotopic compositions (Δ′17O) of DIP relative to VSMOW with the reference line with a slope of 0.528 as an additional tracer to clarify the sources and dynamics of DIP in the hydrosphere. We found significant variation in the Δ′17O values of riverine DIP i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
11
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3
1

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(11 citation statements)
references
References 60 publications
(201 reference statements)
0
11
0
Order By: Relevance
“…Microbial intracellular water can comprise significant fractions of atmospheric oxygen, presenting a distinct mass-independent 17 O anomaly, that is passed onto the respective inorganic and organic phosphorus compounds (Herwartz, 2021). Similarly, atmospheric O 2 carries 17 O anomalies that have been traced in various geological materials (Pack, 2021) and more recently in the hydrosphere (Sambuichi et al, 2023). This 17 O anomaly could also persist in phosphate from ash derived from biomass burning (e.g., wildfires) because phosphate exchanges with air O 2 at elevated temperatures (Bigio & Angert, 2018;Liang & Blake, 2006b).…”
Section: Triple Oxygen Isotope Dynamics and Alternatives To Tc/ea-irmsmentioning
confidence: 99%
“…Microbial intracellular water can comprise significant fractions of atmospheric oxygen, presenting a distinct mass-independent 17 O anomaly, that is passed onto the respective inorganic and organic phosphorus compounds (Herwartz, 2021). Similarly, atmospheric O 2 carries 17 O anomalies that have been traced in various geological materials (Pack, 2021) and more recently in the hydrosphere (Sambuichi et al, 2023). This 17 O anomaly could also persist in phosphate from ash derived from biomass burning (e.g., wildfires) because phosphate exchanges with air O 2 at elevated temperatures (Bigio & Angert, 2018;Liang & Blake, 2006b).…”
Section: Triple Oxygen Isotope Dynamics and Alternatives To Tc/ea-irmsmentioning
confidence: 99%
“…In the mass spectrum for a 50:50 μM mixed solution of phosphate and sulfate, we observed that the relative signal intensity of 1 H 2 P 16 O 4 − was only 37% of that of 1 H 32 S 16 O 4 − under source fragmentation with 0 V (Figure 4A). Since 1 H 32 S 16 When source fragmentation energy was set to 40 V to achieve condition where almost all H 2 PO 4 − ions were converted into PO 3 − ions, the generated SO 3 − ion signal was only half of that of the PO 3 − ion in intensity (Figure 4B). Note that the 32 S 16 O 3 − (m/z = 80) ions do not interfere with the P 16 O 3 − ions (m/z = 79), and the PO 3 − ions become the predominant species in the Orbitrap analyzer.…”
Section: Comparing the Three Different Methodsmentioning
confidence: 99%
“…Since 1 H 32 S 16 When source fragmentation energy was set to 40 V to achieve condition where almost all H 2 PO 4 − ions were converted into PO 3 − ions, the generated SO 3 − ion signal was only half of that of the PO 3 − ion in intensity (Figure 4B). Note that the 32 S 16 O 3 − (m/z = 80) ions do not interfere with the P 16 O 3 − ions (m/z = 79), and the PO 3 − ions become the predominant species in the Orbitrap analyzer. Consequently, we think that the higher PO 3 − fraction in the Orbitrap analyzer results in a higher shot-noise limit precision and better phosphate δ 18 O reproducibility.…”
Section: Comparing the Three Different Methodsmentioning
confidence: 99%
See 2 more Smart Citations